OCCLUSION THERAPY TREATMENT IN AMBLYOPIC EYE - Verma, Dhiraj Kumar (Journal of Biomedical and Pharmaceutical Research, 2018)
“Amblyopia is the most common visual disorder of childhood, yet the contributions of the two principal treatments (spectacle wear and occlusion) to outcome are unknown. The MOTAS study investigated the dose-response relationship between occlusion (patching) and improvement in visual acuity. The use of the Occlusion Dose Monitor (ODM) to record the amount of occlusion dose received by the child represents a major innovation and is unique to these study.The most common causes of visual impairment in adults and children, and visual loss may be permanent if not treated in time. Though many studies have been done on occlusion therapy which is the mainstay in the treatment of unilateral amblyopia, discrepancies exist in literature about quantification of treatment and follow up measures. The present study was undertaken to evaluate the factors responsible for the successful outcome of treatment and the optimum time required for the same in children with unilateral amblyopia.Baseline characteristics of 60 verbal patients with unilateral amblyopia (strabismic, anisometropic, mixed) referred to the Strabismus and Amblyopia Clinic at the Dr. NimeshMathur Centre for Ophthalmic Sciences,Navi Mumbai between September 2016 to December 2017 who improved to the desired level of visual acuity after treatment for amblyopia in the mentioned time period, were analyzed to assess for factors that directly or indirectly influenced the optimum visual rehabilitation and the average duration of therapy required for the same. The evaluation included assessment of the baseline best-corrected visual acuity (BCVA) and refractive status in both eyes, the age at presentation, the type of amblyopia present, fixation pattern in the amblyopic eye, intereye visual acuity difference, and evaluation of compliance through a parental diary system.BCVA in the amblyopic eye was similar in all the three groups. Patients with anisometropicamblyopia showed a quicker response to therapy. Compliance to treatment was the major factor affecting the overall time required for a successful outcome in most cases.